Effects of Job Promotion and Work Motivation on Employee Performance: The Mediating Role of Job Satisfaction at PT BRI Mattoangin Branch - Fadjar Hidayat (Golden Ratio of Data in Summary, 2026)
This study aims to examine and analyze the influence of job promotion and work motivation on employee performance, with job satisfaction serving as an intervening variable at the office of PT Bank Negara Indonesia (Persero) Tbk, Mattoangin Branch. The research was conducted over a two-month period, from October 2025 to November 2025. The population of this study consisted of 118 permanent employees of PT Bank Negara Indonesia (Persero) Tbk, Mattoangin Branch Office. The sampling method employed was saturated sampling, in which all 118 permanent employees were selected as the research sample. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results of this study indicate that job promotion has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, job promotion has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance. Furthermore, job promotion has a positive and significant effect on employee performance through job satisfaction as an intervening variable, and work motivation also has a positive and significant effect on employee performance through job satisfaction as an intervening variable.